AN ANALYSIS OF CLASSROOM STUDENTS’ MISBEHAVIORS IN MECHANICAL ENGINEERING DEPARTMENT CLASS OF GRADE XI IN SMK NEGERI 3 SINGARAJA - Wedhanti, N.K; Sasih, L.L. (International Journal of Language and Literature, 2017)
This descriptive qualitative research was aimed at finding out the kinds of students’ misbehavior in the classroom of Mechanical Engineering Department of grade 11 in SMK Negeri 3 Singaraja, knowing the students’ reasons for doing misbehaviors in the classroom, and also the aim at knowing the teacher’s responses towards the students’ misbehaviors happened in the classroom. The subject of this research was all students in the classroom of Mechanical Engineering Department of grade11 and their English teacher. Observation and interview were the techniques used to collect the data of this research. Descriptive qualitative techniques were then used to analyze the data that was gathered. The result of this research showed that there were ten kinds of students’ misbehavior happened in the classroom of Mechanical Engineering Department grade 11 in SMK Negeri 3 Singaraja. Those misbehaviors were inattention, apathy, needless talk, moving about the room, annoying others, disruption, lying, cheating, aggression and fighting, and also defiance of authority. Six of those misbehaviors happened consistently and four of those misbehaviors happened inconsistently in the classroom. There were found six students’ reasons for doing those ten kinds of misbehavior in the classroom. After that, there were found five teacher’s responses towards misbehaviors done by the students in the classroom of Mechanical Engineering Department of grade 11 in SMK Negeri 3 Singaraja.